The Critical Approach of ‘Plug’ in Re-Conceptualisation of Architectural Program - Bahar Beslioglu (VLC Arquitectura)
This paper explores the issue of ‘plug’ in designing program within particular experimental studies in architecture. There was what could be called a critical ‘elaboration’ of program in Archigram’s 1964 ‘Plug-In’ City project, while intriguingly the critical approach taken in the 2001 ‘Un-Plug’ project of Francois Roche and Stephanie Lavaux hinted at a ‘re-evaluation’ of ‘plug’ related to program in architecture. The embedded criticism and creative programmatic suggestions in both projects will be discussed from the point of view of using the accumulated urbanscape as a potential for contemplation, a theme that has also been elaborated, both theoretically and experimentally, by the artist/architect Gordon Matta-Clark in his 1978 ‘Balloon Housing’ project. These experimentations - about the ‘plug’ - need to be discussed in order to understand their contributions as traceable sources to program issue in contemporary architecture.